Seismic and Fire Assessment and Upgrading Process for Historical Buildings: The Case Study of Palazzo Colonna in Caggiano - Miano, Andrea; de Silva, Donatella; Chiumiento, Giovanni; Capasso, Mario Luca (Frontiers in Built Environment, 2020)
The assessment and retrofit of existing masonry structures with historical and cultural value in highly seismic zones is a challenging issue in earthquake engineering. In fact, the historic and recent earthquakes have showed the problem of the seismic vulnerability of existing masonry constructions. A historical masonry palace, located in Caggiano (Salerno, Italy) is used herein as case study, showing the vulnerability assessment and the seismic upgrading process. The case study building has a masonry structural type at the first two floor while there is a third floor realized in reinforced concrete and a fourth floor realized with a wood structure. The building was characterized by a remarkable seismic vulnerability and needed seismic upgrading operations. After the vulnerability assessment process, some design suggestions are proposed for the seismic upgrading of the building. The structure before and after the upgrading operations has been checked through non linear static and dynamic analyses. Then, coherently with the ”Sismabonus” approach, the attribution of the seismic risk class, performed through numerical analyses, is founded on two parameters, namely the Annual Expected Average Losses (PAM), related to economic factors, and the Life Safety Index (IS-V), related to the structure seismic safety. Finally, the overcoming of the different classes of risk is showed and compared with the amount of the retrofit operations, their costs and the impact on the existing space. Moreover, also fire assessment has been investigated. In fact, in many cases the buildings such as the case study structure are intended to public activities such as museums, so specific fire requirements, like fire resistance, are necessary. This topic became relevant especially if the structure is equipped with particular structural retrofit interventions which can be altered and modified in case of a fire. The paper presents the results of advanced thermo-mechanical analyses on the historical masonry palace under investigation. Since the case study building has a masonry structural type at the first two floor while there is a third floor realized in reinforced concrete, the fire analyses were conducted on the third and on the fourth floors, which may be more vulnerable to fire.